Proteases and their inhibitors involved in Schistosoma mansoni egg-host interaction revealed by comparative transcriptomics with Fasciola hepatica eggs - Peterkova, Kristyna; Vorel, Jiri; Ilgova, Jana; Ostasov, Pavel; Fajtova, Pavla; Konecny, Lukas; Chanova, Marta; Kasny, Martin; Horn, Martin; Dvorak, Jan (International journal for parasitology, 2023)
Schistosoma mansoni eggs are the main causative agents of the pathological manifestations of schistosomiasis. The eggs are laid in the host bloodstream, then they migrate through the intestinal wall into the lumen. However, a significant proportion of the eggs become lodged in the liver, where they cause inflammation and fibrosis. In this study, we focus on a specific group of proteins expressed by the egg, namely proteases and their inhibitors. These molecules are often involved in schistosome-host interactions, but are still unexplored in the egg stage. Using RNA-seq and comparative transcriptomics of immature and mature S. mansoni eggs, we mapped the portfolio of proteases and their inhibitors, and determined their gene expression levels. In addition, we compared these data with gene expression of proteases and their inhibitors in Fasciola hepatica eggs. Fasciola hepatica eggs served as a useful comparative model, as they do not migrate through tissues and inflict pathology. We detected transcription of 135 and 117 proteases in S. mansoni and F. hepatica eggs, respectively, with 87 identified as orthologous between the two species. In contrast, we observed only four orthologous inhibitors out of 21 and 16 identified in S. mansoni and F. hepatica eggs, respectively. Among others, we measured high and developmentally regulated levels of expression of metalloproteases in S. mansoni eggs, specifically aminopeptidase N1, endothelin-converting enzyme 1, and several leishmanolysin-like peptidases. We identified highly transcribed protease inhibitors serpin and alpha-2-macroglobulin that are unique to S. mansoni eggs, and antistasin-like inhibitor in F. hepatica eggs. This study provides new insights into the portfolio of proteases and inhibitors expressed by S. mansoni with potential roles in egg tissue migration, stimulation of angiogenesis, and interaction with host blood and immunity.
Keywords: Transcriptome; Egg; endopeptidasy; Endopeptidases; Animals; schistosomóza; Schistosoma mansoni; Schistosomiasis; Fasciola hepatica; proteasy; Protease; Protease inhibitor; Comparative transcriptomics; zvířata; transkriptom; Peptide Hydrolases